INTERNATIONAL MOBILITY AS A MEANS OF ENSURING INCLUSIVE GLOBAL HIGHER EDUCATION SPACE - Iryna Myhovych (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The paper deals with the notion of international mobility analysed within the context of internationalisation process in higher education as a means of ensuring inclusive global higher education space. International mobility is looked upon as a two-way process - on the one hand, for countries mobility is of vital importance since they are competing to attract top talent and thus benefit economically, diplomatically, and academically in keeping their academic doors open to students from all over the world. On the other hand, students' interest in mobility programmes, international internships and other forms of mobility is growing and has become a crucial component of the current higher education landscape since having the experience of participating in international mobility programmes has an overall positive impact on the development of a wide range of twenty-first-century job skills that result in career promotion. Based on up-to-date statistics an attempt has been made to prove the following - as more countries around the world become active hosts of international students and implement national strategies to attract them, the competition for top global talent in higher education will intensify; as the result, the role of global student mobility and international experiential learning as components of internationalisation process will become more prominent. It has also been stated that as the context of higher education has gradually been changing in the result of international mobility process, comprehensive data is crucial for affirming institutional goals of enhancing internationalisation and correspondingly implementing new policies in order to meet new students' and competitive job market's demands.